THE PARTICIPATION OF UX DESIGNERS IN ARTIFICIAL INTELLIGENCE PROJECTS: RECOMMENDER SYSTEMS - Ruiz, Cinthia; Quaresma, Manuela (Ergodesign & HCI, 2022)
With technological advances, artificial intelligence has gained prominence and we increasingly find innovative products on the market, bringing it as a differential. One example is machine learning-based recommender systems, which filter content in a personalized way for each user, saving the user's time and cognitive effort. Like any novelty, the professional market is still maturing, and users are learning to interact with interfaces. The performance of a UX designer becomes relevant to ensure a good user experience. Therefore, it is important to investigate the market to map the participation of the UX designer in the development of products that use a recommendation system. For this purpose, this research involved market professionals in interviews to understand the UX Designer's participation in developing recommendation systems based on machine learning and identified several relevant issues that point to the need to focus on human factors. It also indicates the training of professionals, the generation of content on the theme of AI/ML aimed at designers and working on the culture of companies.